2014
DOI: 10.1016/j.jcss.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Bounded-width QBF is PSPACE-complete

Abstract: Tree-width is a well-studied parameter of structures that measures their similarity to a tree. Many important NP-complete problems, such as Boolean satisfiability (SAT), are tractable on bounded tree-width instances. In this paper we focus on the canonical PSPACE-complete problem QBF, the fully-quantified version of SAT. It was shown by Pan and Vardi [LICS 2006] that this problem is PSPACE-complete even for formulas whose tree-width grows extremely slowly. Vardi also posed the question of whether the problem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 8 publications
0
37
0
Order By: Relevance
“…After showing that QBF remains PSPACE-complete on graphs of bounded pathwidth [3], the authors introduced a width parameter based on treewidth, which is called respectful treewidth, that allows to take into account dependencies between the variables in a QBF formula. They showed that QBF is fixed-parameter tractable parameterized by respectful treewidth provided that a corresponding tree decomposition is given as part of the input.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…After showing that QBF remains PSPACE-complete on graphs of bounded pathwidth [3], the authors introduced a width parameter based on treewidth, which is called respectful treewidth, that allows to take into account dependencies between the variables in a QBF formula. They showed that QBF is fixed-parameter tractable parameterized by respectful treewidth provided that a corresponding tree decomposition is given as part of the input.…”
Section: Related Workmentioning
confidence: 99%
“…Prominent examples of decompositions used in such techniques include decompositions for the structural parameters treewidth [30], pathwidth [29], clique-width [10] and rankwidth [25]; all of these are known to support FPT algorithms for SAT [38,19], but the same is not true for QBF. Indeed QBF remains PSPACE-complete even on instances with constant pathwidth [3]. As a consequence, many classes of QBFs that have a natural and seemingly "simple" structure remained beyond the reach of current algorithmic techniques; this is also witnessed by previous work of Pan and Vardi [26] that established strong lower bounds for the problem.…”
Section: Introductionmentioning
confidence: 99%
“…We remark that general QBF of bounded treewidth without any restriction on the quantifier prefix is PSPACE-complete [3], and finding tractable fragments by taking into account the structure of the prefix and notions similar to treewidth is quite an active area of research, see e.g. [15,14].…”
Section: Corollary 32mentioning
confidence: 99%
“…Atserias and Oliva [1]) in order to achieve bounded treewidth of the graph used. However, Atserias and Oliva [1] note that bounded treewidth quantified boolean formula become polynomial time solvable when restricted to respectful bounded treewidth instances by a result of Chen and Dalmau [3]. Thus, a potential PSPACE-completeness result for Shortest Path Game on bounded treewidth graphs will likely require a different approach; the computational complexity of Shortest Path Game on bounded treewidth graphs remains an interesting open question.…”
Section: More General Classes Of Graphs and Some Observationsmentioning
confidence: 99%